2006
DOI: 10.1038/oby.2006.227
|View full text |Cite
|
Sign up to set email alerts
|

The Feet of Overweight and Obese Young Children: Are They Flat or Fat?

Abstract: MICKLE, KAREN J., JULIE R. STEELE, AND BRIDGET J. MUNRO. The feet of overweight and obese young children: are they flat or fat ? Obesity. 2006;14:1949-1953. Objective: The purpose of this study was to determine whether the flat feet displayed by young obese and overweight children are attributable to the presence of a thicker midfoot plantar fat pad or a lowering of the longitudinal arch relative to that in non-overweight children. Research Methods and Procedures: Foot anthropometry, an arch index derived from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
159
3
11

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 184 publications
(185 citation statements)
references
References 13 publications
12
159
3
11
Order By: Relevance
“…However, unlike younger overweight and obese children, 3 the obese children in this study had significantly higher feet relative to the feet of the non-obese children. The obese children's feet were higher at the point where the upper surface of the foot meets the leg (dorsal arch) and also higher at the front of the foot (ball of foot).…”
Section: External Foot Measurescontrasting
confidence: 69%
See 2 more Smart Citations
“…However, unlike younger overweight and obese children, 3 the obese children in this study had significantly higher feet relative to the feet of the non-obese children. The obese children's feet were higher at the point where the upper surface of the foot meets the leg (dorsal arch) and also higher at the front of the foot (ball of foot).…”
Section: External Foot Measurescontrasting
confidence: 69%
“…8,9 A recent study confirmed thicker fat padding in the feet of obese, compared to overweight, school-aged children, although as the between-group difference was small, no functional relevance was attributed to this increased fat pad thickness. 10 However, in a study comparing preschool children, 3 no difference in medial fat pad thickness was found between overweight/obese and non-overweight participants. As significant between-group differences were evident in external arch height measures in these two previous studies, the authors postulated that obese children's feet were structurally flatter, rather than fatter, than their leaner counterparts.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Initial treatment options include activity modification, proper shoe and orthoses, exercises and medication (Halabchi et al 2013). In the neonates and toddlers, it is known that a fat pad is present underneath the medial longitudinal arch of the infant foot while the arch develops; although this fat pad is thought to resolve between the ages of 2 and 5 years as the arch of the foot is formed (Mickle et al 2006). Different studies (Cheng et al 1997;Hernandez et al 2007;Morrison et al 2007;Chen et al 2009) on measurements of foot have been conducted in worldwide scenario among the children and adult population.…”
Section: Introductionmentioning
confidence: 99%
“…Although feet that are structurally sound can perform daily tasks with ease, deviations from normal foot structure can compromise foot function and, in turn, cause discomfort and/or pain [6]. Extensive research has confirmed that overweight and obesity negatively affect foot structure and function in children, whereby obese children have been found to have flatter feet and generate significantly higher plantar pressures during walking relative to non-overweight children [7][8][9][10][11][12][13]. High plantar pressures, which describe the potential damaging effects of increased load on the plantar tissues [14], have been found to correlate with reduced physical activity and more time spent in sedentary behaviour, possibly due to foot pain and discomfort experienced during weight-bearing activities [15].…”
Section: Introductionmentioning
confidence: 99%